(untitled) (Malaysian Journal of Civil Engineering, 2017)
Research has been carried out to establish an experimentally based effective stress volumettic compression model for isotropically and anisotropically consolidated Keuper marl silt subjected to undrained cyclic loading with drainage rest-periods [Marto (1996)]. The experimental programme included monotonic strain controlled triaxial tests and three stages of undrained two-way cyclic loading wilh drained rest-periods. The monotonic strain controlled triaxial tests on both isotropic ally and anisotropically, normally and overconsoidatcd silt were carried out to establish the critical state boundary surface of the soil. This critical state boundary surface was used as a framework for cyclic loading tests. This paper will discuss the development of critical state parameters and the critical state boundary surface for the investigated material.